2022
DOI: 10.3389/fendo.2022.835154
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Insulin Resistance Is Positively Associated With Serum Uric Acid Levels and Hyperuricemia in Northern Chinese Adults

Abstract: ObjectiveAdipose tissue plays a crucial role in serum uric acid (UA) metabolism, but the relative contribution of adipose tissue insulin resistance (IR) to serum UA levels and hyperuricemia have not explicitly been illustrated. Herein, we aimed to investigate the association between the adipose tissue insulin resistance index (Adipo-IR) and hyperuricemia in this cross-sectional study. The homeostasis model assessment of insulin resistance (HOMA-IR) index, another widely applied marker to determine systemic IR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Although some studies have explored the correlation between IR and HU, studies comparing the prediction ability of different IR indicators in patients with HU remain rare ( 9 , 10 ). In addition, previous studies mainly focus on the general population including diabetics, ignoring the potential risk of IR in non-diabetic populations with HU ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have explored the correlation between IR and HU, studies comparing the prediction ability of different IR indicators in patients with HU remain rare ( 9 , 10 ). In addition, previous studies mainly focus on the general population including diabetics, ignoring the potential risk of IR in non-diabetic populations with HU ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic high SUA concentrations cause a pro-inflammatory state in adipose tissue by inducing the release of monocyte chemoattractant protein 1, inducing a vicious cycle [ 33 ]. In addition, studies have shown that adipose tissue produces UA [ 36 ]. The activity of the enzyme xanthine oxidoreductase, which converts xanthine and hypoxanthine to UA, is high during obesity [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that adipose tissue produces UA [ 36 ]. The activity of the enzyme xanthine oxidoreductase, which converts xanthine and hypoxanthine to UA, is high during obesity [ 33 , 36 ]. Compared to normal-weight children, obese children have higher SUA concentrations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“… 52 The increased SUA level may be related to visceral adipose inflammation induced IR. 53 Sun et al 54 showed that adipose tissue IR (Adipo-IR), HOMA-IR, and SUA were closely related. However, HOMR-IR was not correlated with HUA in men with a normal BMI (18.5 kg/m 2 ≤ BMI < 24 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%